PSYCHOLOGICAL CHARACTERISTICS OF ADOLESCENTS IN PARENTAL CARE (Multidisciplinary Journal of Science and Technology, 2024)
The article examines the features of psychological counseling to parents on issues of irresponsibility and lack of independence of teenagers. During consultations between the teacher-psychologist and parents of teenagers, constructive methods of interaction, options for carrying out preventive and educational work with parents of teenagers are offered. With parents and teenagers recommendations on the contents of preventive and educational trainings are given.